Search for charginos, neutralinos and gravitinos at LEP - Abreu, P; Adam, W; Adye, T; Ajinenko, I; Alekseev, G; Alemany, R; Allport, P; Almehed, S; Amaldi, U; Amato, S; Andersson, P; Andreazza, A; et al. (1998)
An update of the searches for charginos and neutralinos in DELPHI is presented, based mainly on recent data collected at centre-of-mass energies of 161 GeV and 172 GeV. No signal is found. For a sneutrino with mass above 300 GeV/c2 and a mass difference between the chargino and the lightest neutralino above 10 GeV/c2, the lower limit at 95% confidence level on the chargino mass ranges from 84.3 GeV/c2 to the kinematical limit (86.0 GeV/c2), depending on the mixing parameters. The limit decreases for lower chargino-neutralino mass differences. The limit in the case of a light sneutrino is 67.6 GeV/c2, provided that that there is no light sneutrino with a mass within 10 GeV/c2 below the chargino mass. Upper limits on neutralino pair production cross-sections of about a picobarn are derived. The (μ, M2) domain excluded in the MSSM-GUT scenario is determined by combining the neutralino and chargino searches. These results imply a limit on the mass of the lightest neutralino which, for a heavy sneutrino, is constrained to be above 24.9 GeV/c2 for tanβ ≥ 1. The search has also been extended to the case where the lightest neutralino is unstable and decays into a photon and a gravitino.